The politics of injustice: Sex-working women, feminism and criminalizing sex purchase in Ireland - McGarry, Kathryn (Criminology & criminal justice, 2019)
This article interrogates the discursive framing of recent law and policy debates on criminalizing sex purchase in Ireland and the implications this has for sex workers’ political voice. Drawing on Nancy Fraser’s work on the political dimensions of justice, we look at how Irish neo-abolitionists, through their Turn Off the Red Light (TORL) campaign, map and delimit access to political space and consequently misframe, misrecognize and misrepresent the ‘problem’ of sex work and sex-working women. We employ the methodological framework suggested by Carol Bacchi’s What’s the Problem Represented to Be (WPR) approach to explore how TORL campaigners exercise and manage frame-setting in law and policy contexts to deny all ‘other’ voices parity of participation in political space. We argue these misframing strategies reflect meta-political injustices of misrepresentation.